I04 AAV5-MIHTT gene therapy demonstrates broad distribution and strong human mutant huntingtin lowering in a huntington disease minipig model. (September 2018) - Klima, Jiri; Evers, Melvin M; Miniarikova, Jana; Juhas, Stefan; Vallès, Astrid; Bohuslavova, Bozena; Juhasova, Jana; Skalnikova, Helena Kupcova; Vodicka, Petr; Valekova, Ivona; Brouwers, Cynthia; Blits, Bas; et al.
Abstract : Background: Huntington disease (HD) is a fatal neurodegenerative disorder caused by a CAG trinucleotide repeat expansion in the huntingtin gene. Great effort has been put in proof-of-concept studies of therapeutic agents in HD rodent models. One of the challenges of rodents as a model of neurodegenerative diseases is their relatively small brain, making successful translation to the HD patient difficult. This is particular relevant for gene therapy approaches, where distribution achieved upon local administration into the parenchyma is likely dependent on brain size and structure. Aims: Here, we investigated the feasibility, efficacy, and tolerability of huntingtin-lowering gene therapy in a large animal brain. Methods: Transgenic HD (tgHD) minipigs were injected with an engineered microRNA targeting human huntingtin, delivered via adeno-associated viral vector serotype 5 (AAV5-miHTT) or AAV5-GFP as control. The viruses were intracranially administered into the striatum and thalamus. Results: We detected widespread dose-dependent distribution of AAV5-miHTT throughout the tgHD minipig brain that correlated with the engineered microRNA expression. Both human mutant huntingtin mRNA and protein were significantly reduced in all brain regions transduced by AAV5-miHTT. Conclusion: The combination of widespread vector distribution and extensive huntingtin lowering observed with AAV5-miHTT supports the translation of a huntingtin-lowering gene therapy for HD from preclinical studies into the clinic.